Robust distributed linear parameter estimation in wireless sensor network - Panigrahi, T.; Mulgrew, B.; Majhi, B. (2011 International Conference on Energy, Automation, and Signal, 2011)
In a wireless sensor network each sensor node collects scalar measurements of some unknown parameters, corrupted by independent Gaussian noise. Then the objective is to estimate some parameters of interest from the data collected across the network. In this paper a simple iterative robust distributed linear parameter estimation algorithm is proposed where the diffusion co-operation scheme is incorporated. Each node updates its information by using the data collected by it and the information received from the neighbours. When any node fails to transmit correct information to the neighbours and/or the data collected by the node is noisy then the least mean square based diffusion estimation is not accurate. Hence a robust diffusion linear estimation algorithm is proposed here in order to improve the accuracy of the estimation in distributed wireless sensor network.